Aspek hukum keperdataan terhadap pemenuhan hak restitusi dalam perkara tindak pidana - Wardatul Fitri; FX Djoko Priyono; Bambang Eko Turisno (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze criminal law enforcement that has occurred and has fulfilled the community's sense of justice (victims of criminal acts and the contribution of civil law science in the practice of criminal law enforcement). The research was conducted qualitatively by using a statutory approach and normative juridical research. The results of the research show firstly that the practice of enforcing criminal law based on Law Number 8 of 1981 concerning the Criminal Procedure Code as a formal law still emphasizes